UPAYA HUKUM ISTERI PERTAMA TERHADAP PERKAWINAN KEDUA SUAMI YANG DILAKUKAN DIBAWAH TANGAN DI DESA NANGA SURUK - SUTRIWAHYUNI NIM. A1011181185 (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstrac Marriages that are not registered are called marriages under the question. Underhand marriage is a marriage which is carried out in accordance with the pillars of marriage according to the Islamic religion but is not registered at the Office of Religious Affairs as regulated in the Marriage Law Number ! 1974 Article 2 paragraph (2). In the Marriage Law Number | 1974 Article 2 paragraph (2) states that marriage is legal if it is carried out according to the laws of each religion and belief. And every marriage is registered according to the applicable laws and regulations. Based on the description of the background above, the author will discuss the problem with the formulation of the problem, namely